Analysis Of Forest And Land Fire Prevention And Law Enforcement Strategies In The Riau Islands In An Effort To Deal With Environmental Crises and Economic Losses: Research Study In Bintan Regency - Edy Supandi; Parameshwara Parameshwara; Darwis Anatami; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Forest and land fires are a serious problem that has a negative impact on the environment and the economy, especially in the Riau Islands region, including Bintan Regency. The background of this research is the high frequency of forest fires that cause ecosystem damage, air pollution, and significant economic losses. This study aims to analyze the forest and land fire prevention and law enforcement strategies that have been implemented and identify obstacles in their implementation. The research method used is qualitative with a case study approach. The data was collected through in-depth interviews with law enforcement officials, forestry officers, and local communities, as well as analysis of documents related to forest fires in Bintan over the past few years. In addition, questionnaires were also distributed to get a broader perspective on the effectiveness of existing strategies. The results of the study show that although there have been various prevention efforts such as routine patrols, socialization, and the installation of prohibition signs, the effectiveness is still not optimal. The main obstacles identified include limited resources, lack of community participation, difficulty in identifying perpetrators, hard-to-reach terrain, and pressure from certain parties. The lack of resources such as personnel and equipment, as well as the low level of public awareness and participation in forest fire prevention, are the main factors hindering the effectiveness of these strategies. In addition, pressure from landowners or influential parties often hinders firm and fair law enforcement. Suggestions for improving the effectiveness of prevention and enforcement strategies include increasing the budget and capacity of officers, the use of advanced technology for monitoring and investigation, and education and empowerment of local communities. In addition, there is a need for increased coordination between agencies and legal protection for officers who face pressure in carrying out their duties. With a comprehensive and inclusive approach, it is hoped that forest and land fires in Bintan can be minimized, so that a more sustainable environment and a stable economy can be realized